Appropriate Approaches in the Territorial Perspective for Reducing the Earthquake Risk in the Urban, Semi-Urban, and Rural Settings of Mid-Western Region of Nepal - Singh, Ramesh Prasad; Praveen, B. M.; Shrestha, Diwat Kumar (International Journal of Atharva, 2025)
This study explores appropriate, territory-specific approaches to earthquake risk reduction in the urban, semi-urban, and rural settings of Nepal's Mid-Western Region. Using empirical data derived from perceptions, preparedness actions, institutional capacity, and governance systems; the analysis reveals significant spatial disparities in how communities experience and respond to earthquake risks. Semi-urban areas, in particular, emerge as a critical zone of vulnerability due to inadequate attention in disaster planning, weak governance capacity, and hybrid infrastructural challenges. The findings emphasize that risk reduction measures must be context-sensitive and aligned with local geographical, institutional, and social realities. The study concludes that strengthening territorial disaster resilience requires a nuanced, inclusive, and decentralized approach that integrates policy enforcement, technical support, and community participation across all settlement types.